Mengembangkan Keterampilan Motorik Anak Usia 5-6 Tahun melalui Kegiatan Pentas Seni Tari di TK Istiqomah - Hilda Zahra Lubis; Andriani Marshanda Lubis; Ririn Marheni Br Barus; Sarina Wahyuni; Seri Rezjeki Wardani Tamba (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
This study aims to develop gross motor skills of children aged 5–6 years through dance performance activities at Istiqomah Kindergarten. Dance activities were chosen because they involve structured and rhythmic body movements, which contribute positively to children's motor development. This study used a descriptive qualitative approach with observation, interviews, and documentation as data collection techniques. The results showed that through routine dance practice and the implementation of art performances, children showed an increase in their ability to coordinate movement, balance, and body flexibility. This activity also increased children's self-confidence and ability to work together. Thus, dance performance activities are effective in supporting the development of gross motor skills in early childhood.